Mitochondrial DNA analyses reveal low genetic diversity in Culex quinquefasciatus from residential areas in Malaysia. Issue 2 (15th July 2013) - LOW, V. L.; LIM, P. E.; CHEN, C. D.; LIM, Y. A. L.; TAN, T. K.; NORMA‐RASHID, Y.; LEE, H. L.; SOFIAN‐AZIRUN, M.
Abstract The present study explored the intraspecific genetic diversity, dispersal patterns and phylogeographic relationships of Culex quinquefasciatus Say (Diptera: Culicidae) in Malaysia using reference data available in GenBank in order to reveal this species' phylogenetic relationships. A statistical parsimony network of 70 taxa aligned as 624 characters of the cytochrome c oxidase subunit I (COI) gene and 685 characters of the cytochrome c oxidase subunit II (COII) gene revealed three haplotypes (A1–A3) and four haplotypes (B1–B4), respectively. The concatenated sequences of both COI and COII genes with a total of 1309 characters revealed seven haplotypes (AB1–AB7). Analysis using tcs indicated that haplotype AB1 was the common ancestor and the most widespread haplotype in Malaysia. The genetic distance based on concatenated sequences of both COI and COII genes ranged from 0.00076 to 0.00229. Sequence alignment of Cx. quinquefasciatus from Malaysia and other countries revealed four haplotypes (AA1–AA4) by the COI gene and nine haplotypes (BB1–BB9) by the COII gene. Phylogenetic analyses demonstrated that Malaysian Cx. quinquefasciatus share the same genetic lineage as East African and Asian Cx. quinquefasciatus. This study has inferred the genetic lineages, dispersal patterns and hypothetical ancestral genotypes of Cx. quinquefasciatus.